Simulation and experimental study of asymmetric split and recombine micromixer with D‐shaped sub‐channels. (6th March 2019) - He, Xiuhua; Xia, Tian; Gao, Linfeng; Deng, Zhidan; Uzoejinwa, Benjamin B.
Abstract : An effective passive micromixer based on the principles of asymmetric split and recombine has been designed, developed, and investigated to enhance the mixing performance of the micromixer in a microfluidic system. The effects of geometrical parameters and the number of mixing units on mixing performance were studied at different Reynolds (Re) number (ranging from 1 to 80) via CFD software ANSYS CFX. The results revealed that the preferable number of mixing units is 6, and the optimal direction of reducer is opposite to the main channel flow; the D‐shaped mixing channel forces the mixed fluid to produce the extended vortex and Dean vortices simultaneously which caused a strong collision at the confluence of fluids, thus leading to the superposition and enhancement of the vortex system; when Re number is 80 and the width ratio of mixing channel W 2/ W 3 = 1, the mixing efficiency of micromixer can exceed 95%.